Lactobacillus rhamnosus strain GG is a potential probiotic for calves - Ewaschuk, Julia B. (Canadian Veterinary Medical Association, 2004)
Diarrhea is a common occurrence in neonatal calves. Several veterinary probiotics claiming to prevent or treat calf diarrhea are available, but have not been well studied. This study assessed the capability of Lactobacillus rhamnosus strain GG (LGG) to maintain viability in the gastrointestinal tract of calves. We also determined whether LGG can be administered in an oral rehydration solution (ORS) without compromising the efficacy of the ORS or the viability of LGG, and whether LGG produces D-lactate or not. To investigate the intestinal survival of LGG, 15 calves were randomized into 3 groups and LGG was administered orally with their morning milk feeding on 3 consecutive days at a low (LD), medium (MD), or high (HD) dosage. Fecal samples were collected on days 0 (control), 1, 2, 3, 5, and 7 and incubated for 72 h on deMan, Rogosa, Sharpe agar. Twenty-four hours after the 1st feeding, LGG was recovered from 1 out of 5 calves in the LD group, 4 out of 5 calves in the MD group, and 5 out of 5 calves in the HD group. To determine if LGG caused the glucose levels in the ORS to drop below effective levels, 1.5 L of the ORS was incubated with LGG for 2 h at 37°C and the glucose concentration was measured every 20 min using a glucose meter. This ORS was then further incubated for 10 h and aliquots analyzed by high performance liquid chromatography to determine if D-lactate was produced by LGG. Glucose concentrations did not change over the 2 h of incubation, and no D-lactate was produced after 48 h. The LGG maintained viability in ORS. Therefore, this study demonstrated that LGG survives intestinal transit in the young calf, produces no D-lactate, and can be administered in an ORS.